Dinamika Karbon dan Mikroba dalam Tanah pada Perlakuan Biochar Kompos Plus - Purbalisa, Wahyu; Zulaehah, Ina; Paputri, Dolty Melyga W.; Wahyuni, Sri (Universitas Diponegoro, 2020)
Carbon and microbes in the soil fluctuated from time to time due to various things. This study aims to determine the dynamics of carbon and microbes in the soil in the treatment of biochar-compost. In addition to the use of biochar-compost, this research also uses nano biochar and enrichment with microbial consortia. The study was conducted at the screen house using a complete randomized design with three replications with following treatments: control / without organic fertilizer (P0), compost (P1), biochar-compost 1: 4 (P2), nano-biochar-compost 1: 4 (P3 ), biochar-compost + microbial consortia (P4), compost + microbial consortia (P5) and biochar-compost + microbial consortia (P6) with a dose of 2.5 tons/ha respectively. Biochar comes from corncobs. Compost biochar plus application was made before planting.Â Parameters observed were soil carbon (C-organic), soil acidity (pH) at 7 DAA, 37 DAA and after harvest, and the total soil microbial population at 2 DAA and after harvest. Soil carbon was measured using Walkey and Black method measured by spectrophotometer, soil pH using a soil: water ratio = 1: 5 and measured by a pH meter, the total microbial population using Total Plate Counting (TPC) method. The results showed carbon and soil microbial populations decreased over time, except for microbial communities in a single compost treatment.